The Sketch. (Londen : Illustrated London News Company, 1893)
The Sketch was a British illustrated weekly journal, which focused on high society and the aristocracy. It ran for 2,989 issues between 1 February 1893[1] and 17 June 1959. It was published by the Illustrated London News Company and was primarily a society magazine with regular features on royalty and the aristocracy, theatre, cinema and art studies. It had a high photographic content with many studies of society ladies and their children as well as regular layouts of point to point racing meetings and similar events. (Wikipedia)
Https://en.wikipedia.org/wiki/The_Sketch
1898: The Internet Archive has volume 22, covering April 27 to July 20, 1898
Engels
Tijdschriften